LITERASI KEUANGAN MENCIPTAKAN KESEJAHTERAAN UMAT KATOLIK - Hateyong, Elizabeth (LOGOS: JURNAL PENDIDIKAN KEAGAMAAN KATOLIK, 2022)
Financial literacy is one of the focus point in this research. This because the knowledge of financial literacy of Indonesian people is poor. Financial literacy create prosperity for the people in the catholic church in this case. The church should be involved at the social and economic problems of these people. Financial literacy will be a first step in the developement to apply in catholic people lifes. Key word: Financial Literacy, Catholic people